2015
DOI: 10.1371/journal.pone.0135334
|View full text |Cite
|
Sign up to set email alerts
|

Local Variability Mediates Vulnerability of Trout Populations to Land Use and Climate Change

Abstract: Land use and climate change occur simultaneously around the globe. Fully understanding their separate and combined effects requires a mechanistic understanding at the local scale where their effects are ultimately realized. Here we applied an individual-based model of fish population dynamics to evaluate the role of local stream variability in modifying responses of Coastal Cutthroat Trout (Oncorhynchus clarkii clarkii) to scenarios simulating identical changes in temperature and stream flows linked to forest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 71 publications
0
31
0
Order By: Relevance
“…Penaluna et al. () found that variability in habitat conditions mediated the response of Cutthroat Trout ( Oncorhynchus clarkii ) to climate change in northwestern Oregon. Boughton et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Penaluna et al. () found that variability in habitat conditions mediated the response of Cutthroat Trout ( Oncorhynchus clarkii ) to climate change in northwestern Oregon. Boughton et al.…”
Section: Discussionmentioning
confidence: 99%
“…, Railsback and Harvey , Piou and Prévost , Penaluna et al. ). The role of stream network topology was investigated by Leibowitz and White () in a life cycle model to better understand Coho Salmon ( Oncorhynchus kisutch ) population dynamics, but they did not consider effects of decisions made by individual fish.…”
Section: Introductionmentioning
confidence: 99%
“…Aquatic-obligate cold-and cool-water species may be particularly vulnerable to the effects of climate change because they require cold, connected, and high-quality habitats. Under contemporary climate change, fish and amphibians are shifting, including range contractions (e.g., Araújo et al 2006;Wenger et al 2010), fluctuations in phenology (Parmesan and Yohe 2003), and reductions in body size (Penaluna et al 2015b). As climate change continues into the future, extinctions of life-history forms and species can be anticipated, especially because high endemism is characteristic of aquatic organisms.…”
Section: Climate Changementioning
confidence: 99%
“…Interactions among threats have become increasingly apparent in recent years; hence, it is critical to recognize cumulative effects when considering the status and persistence of Pacific trout (Bisson et al 1992;Schindler 2001;Penaluna et al 2015).…”
Section: Current and Future Threatsmentioning
confidence: 99%
“…For some streams, there is increasing evidence for elevated stream temperatures Arismendi et al 2012) and reductions in flows (Luce and Holden 2009;Safeeq et al 2013) across western North America. Combined with other threats, these climateinduced changes will continue to have noticeable effects on Pacific trout distribution (Rahel et al 1996;Wenger et al 2011;Roberts et al 2013), demography (Al-Chokhachy et al 2013;Quiñones et al 2014;except Penaluna et al 2015), phenology (Kovach et al 2013;Penaluna et al 2015), and genetic diversity . Pacific trout are especially vulnerable to the effects of climate change in freshwater habitats because they require cold, interconnected, and high-quality habitats, which have already been fragmented and degraded by other anthropogenic activities in many areas.…”
Section: Climate Changementioning
confidence: 99%